Influence of electrospray deposition on C(60) molecular assemblies - Hinaut, Antoine (Beilstein J Nanotechnol, 2021)
Maintaining clean conditions for samples during all steps of preparation and investigation is important for scanning probe studies at the atomic or molecular level. For large or fragile organic molecules, where sublimation cannot be used, high-vacuum electrospray deposition is a good alternative. However, because this method requires the introduction into vacuum of the molecules from solution, clean conditions are more difficult to be maintained. Additionally, because the presence of solvent on the surface cannot be fully eliminated, one has to take care of its possible influence. Here, we compare the high-vacuum electrospray deposition method to thermal evaporation for the preparation of C(60) on different surfaces and compare, for sub-monolayer coverages, the influence of the deposition method on the formation of molecular assemblies. Whereas the island location is the main difference for metal surfaces, we observe for alkali halide and metal oxide substrates that the high-vacuum electrospray method can yield single isolated molecules accompanied by surface modifications.